Catalytic Oxidative Deamination by Water with H(2) Liberation - Tang, Shan (J Am Chem Soc, 2020)
[Image: see text] Selective oxidative deamination has long been considered to be an important but challenging transformation, although it is a common critical process in the metabolism of bioactive amino compounds. Most of the synthetic methods developed so far rely on the use of stoichiometric amounts of strong and toxic oxidants. Here we present a green and efficient method for oxidative deamination, using water as the oxidant, catalyzed by a ruthenium pincer complex. This unprecedented reaction protocol liberates hydrogen gas and avoids the use of sacrificial oxidants. A wide variety of primary amines are selectively transformed to carboxylates or ketones in good to high yields. It is noteworthy that mechanistic experiments and DFT calculations indicate that in addition to serving as the oxidant, water also plays an important role in assisting the hydrogen liberation steps involved in amine dehydrogenation.